A Novel Still Image Error Concealment Using Fragile Watermarking in Wireless Image , Transmission and Packet-Switched Networks - Davood Bashiri; Ali Aghagolzadeh; Javad Musevi niya; Mahdi Nooshyar (International Journal of Information and Communication Technology Research, 2009)
In this paper, we propose a new error concealment method for covering up the high packet losses of an original image after its transmission through an error-prone channel. Our proposed technique utilizes, Discrete Wavelet Transform (DWT) to produce a lower resolution copy of the original image. Then we embed some o'f discrete cosine transform (DCT) coefficients of this downsized replica of the original image into the original image in the spatial (pixel) domain inside macroblocks (MBs) as a watermark. This technique can be implemented for error-prone channels to combat degradations due to packets loss in a backward-compatible scheme.